Identification of the protein coding capability of coronavirus defective viral genomes by mass spectrometry - Lin, Ching-Hung; Hsieh, Feng-Cheng; Lai, Chien-Chen; Wang, Wei-Chen; Kuo, Cheng-Yu; Yang, Chun-Chun; Hsu, Hsuan-Wei; Tam, Hon-Man-Herman; Yang, Cheng-Yao; Wu, Hung-Yi (Virology journal, 2023)
During coronavirus infection, in addition to the well-known coronavirus genomes and subgenomic mRNAs, an abundance of defective viral genomes (DVGs) can also be synthesized. In this study, we aimed to examine whether DVGs can encode proteins in infected cells. Nanopore direct RNA sequencing and liquid chromatography-tandem mass spectrometry (LC–MS/MS) analysis were employed. With the protein databases generated by nanopore direct RNA sequencing and the cell lysates derived from the RNA–protein pull-down assay, six DVG-encoded proteins were identified by LC–MS/MS based on the featured fusion peptides caused by recombination during DVG synthesis. The results suggest that the coronavirus DVGs have the capability to encode proteins. Consequently, future studies determining the biological function of DVG-encoded proteins may contribute to the understanding of their roles in coronavirus pathogenesis and the development of antiviral strategies.